2018
DOI: 10.1039/c8tc02193g
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the silent upconversion emissions from a single β-NaYF4:Yb/Er microcrystal via saturated excitation

Abstract: Achieving intense nearly white upconversion emission from a single β-NaYF4:Yb/Er microcrystal via saturated excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…This causes the red and green UCL compete to each other. This experimental phenomenon is similar to our previous literature reported that the highly-Yb 3+ doped NaYF4:Er microcrystals always tend to generate red UCL color under 980 nm excitation [23]. However, for lowly Yb 3+ -doped NaYF4:2%Er microcrystal, there is no CR processes occurrence because of the relatively far distance between Yb 3+ and Er 3+ ions.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This causes the red and green UCL compete to each other. This experimental phenomenon is similar to our previous literature reported that the highly-Yb 3+ doped NaYF4:Er microcrystals always tend to generate red UCL color under 980 nm excitation [23]. However, for lowly Yb 3+ -doped NaYF4:2%Er microcrystal, there is no CR processes occurrence because of the relatively far distance between Yb 3+ and Er 3+ ions.…”
Section: Resultssupporting
confidence: 90%
“…The β-NaYbF4:Er microcrystals were synthesized by the similar hydrothermal method procedure according to our previous study [23]. In a typical procedure, for instance, synthesis of the β-NaYbF4:2%Er (mol%) microcrystals: firstly, the Yb(NO3)3 and Er(NO3)3 powders were dissolved in deionized water yielding a clear solution of Ln(NO3)3 (0.2 M); then the EDTA-2Na (1 mmol) and NaOH (5 mmol) were mixed with 12.5 mL deionized water under continuously stirring in a beaker; following, 5 mL of Ln(NO3)3 (0.2 M) aqueous solutions (the total Ln 3+ is 1 mmol), 8 mL of NH4F (2.0 M) aqueous solutions and 7 mL of dilute hydrochloric acid (1 M) were added into the beaker; finally, the above mixtures were stirred for 1.5 hour and transferred into a 50 mL Teflon-lined autoclave and heated at 200°C for 40 hours.…”
Section: Synthesis Of β-Naybf4 Microcrystalsmentioning
confidence: 99%
“…These new UC emissions can be detected both in Mn-free and highly Mn 2+ -doped microcrystals. As demonstrated in our previous study [35], these new UC emissions originate from the transitions of 4 G 11/2 → 4 I 15/2 (382 nm), 4 F 5/2 → 4 I 15/2 (457 nm), 2 K 15/2 → 4 I 13/2 (472 nm), 4 G 11/2 → 4 I 15/2 (506 nm), 2 H 9/2 → 4 I 13/2 (560 nm), and 4 G 11/2 → 4 I 11/2 (618 nm) in Er 3+ , respectively. It is noteworthy that the newly emerged UC emissions can be observed regardless of the Mn 2+ concentration and the new 560 nm emission is always stronger than the traditional green (545 nm) emission.
Fig.
…”
Section: Resultssupporting
confidence: 67%
“…In comparison with these three UC emissions, other UC emissions are rarely observed in Yb/Er co-doped materials. Previously, we have observed a newly emerged 560 nm ( 2 H 9/2 → 4 I 13/2 ) emission from a single β-NaYF 4 :Yb/Er microcrystal under saturated excitation [ 35 ]. As excitation intensity increases, the 560-nm emission increases rapidly and further exceeds the traditional green emission (545 nm).…”
Section: Introductionmentioning
confidence: 99%
“…[46] Changing the excitation wavelength and power, or utilizing pulse excitation with tunable pulse width and frequency obviously affects the excitation process and thus the emission properties, not only intensity and color, but also decay time. Similar exploratory work by other groups has extended the upconversion excitation wavelength from 980 to 800 and 1532 nm, and achieved multicolor upconversion luminescence through controlling the excitation wavelength [48][49][50][51] ; Yuan et al [52] observed and intensified the silent upconversion emission bands of Er 3+ at 382, 472, 506, 560, and 618 nm from a single NaYF 4 :Yb/Er microcrystal via increasing the excitation power. Similar exploratory work by other groups has extended the upconversion excitation wavelength from 980 to 800 and 1532 nm, and achieved multicolor upconversion luminescence through controlling the excitation wavelength [48][49][50][51] ; Yuan et al [52] observed and intensified the silent upconversion emission bands of Er 3+ at 382, 472, 506, 560, and 618 nm from a single NaYF 4 :Yb/Er microcrystal via increasing the excitation power.…”
Section: Introductionmentioning
confidence: 69%